The Socialist People's Libyan Arab Jamahiriya : 2005 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This 2005 Article IV Consultation underlies that in 2004, Libya's macroeconomic performance was satisfactory, owing mainly to higher oil prices and increased oil output. Real GDP grew 4 1\2 percent while consumer prices declined. The favorable developments in the oil market contributed to a significant improvement in the external current account surplus, which reached some 24 percent of GDP. In 2005, macroeconomic performance remained relatively strong. Real GDP growth was about 3 1\2 percent, and inflation low. In contrast to previous years, economic growth is estimated to have been generated mainly in the non-oil economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet